Application of Liquid Organic Fertilizer on Sandalwood (Santalum album L.) invitro from East Nusa Tenggara - Solle, Hartini (Al-Hayat: Journal of Biology and Applied Biology, 2022)
Sandalwood (Santalum album L.) which grows in East Nusa Tenggara is an endemic plant known as hau meni. Sandalwood is used as a base for carving and perfume containing essential oils that have a distinctive aroma. The superiority that is owned causes the selling price is very expensive. This causes exploitation which results in a diminishing number of Sandalwood trees. Efforts to replant have been carried out through seedlings and nurseries but the success rate is still low. Efforts through invitro are expected to help conserve this plant. To determine the effect of giving Liquid Organic Fertilizer (LOF) on the growth of Sandalwood and the best concentration in promote germination. The study was conducted by adding different types of LOF with concentration variation. The addition of Nasa with a concentration of 2 mL which is the optimal concentration in promote the germination with the response at 14 Days After Planting (DAP) on Murashige and Skoog (MS) medium while on the addition of lontar the concentration of 2 mL shows the response of the appearance of plumula. The addition of base type LOF on MS medium affected 82% germination percentage while lontar type LOF stimulated vegetative growth of Sandalwood plants.